Cold Agglutinin Disease Unfurled in Laboratory and Blood Bank: A Little Poignant Observation Can Speak a Lot! - Archana Shetty; Gurudatta Murthy; Bharadwaj Golithadka (Archives of Medicine and Health Sciences)
Autoimmune hemolytic anemias (AIHAs) are hemolytic anemias characterized by the production of autoantibodies against surface antigens on red blood cells. Cold agglutinin disease (CAD) is a relatively rare subcategory of AIHA, affecting mainly the middle-aged with anemia often being the presenting symptom. We present a case of a middle-aged female who was admitted for severe anemia under evaluation. A discrepancy in blood grouping was noted when request for blood transfusion was received in a blood bank, owing to autoantibodies interfering in testing. Routine complete blood counts showed temperature-based variations. A detailed workup confirmed a diagnosis of CA type of AIHA. The case reiterates the importance of good interdepartmental coordination between clinicians, laboratory, and blood bank, which helped clinch the diagnosis of CAD through the correlation of clinical findings, blood counts, and immunological and biochemical parameters.